Clinical-epidemiological and treatment characteristics of children with COVID-19 in a tertiary referral center in Perú: Características clínicas de niños con COVID-19 admitidos en un centro terciario de referencia en el Perú - Chiara Chilet, Christian (2022)
Introduction: The COVID-19 pandemic has a great impact on children's health. This study describes the characteristics of hospitalized children at the San Borja National Children's Health Institute in Perú. Methods: This was a retrospective study of patients with a confirmed diagnosis of COVID-19 from March to July 2020. Demographic, clinical, laboratory, radiological, and treatment information were collected. Data analysis included descriptive statistics and bivariate analysis to determine differences between patients in general wards and the intensive care unit (ICU).   Results: We included 91 patients, 33 being females (36.3%). The most affected age group was children > 2 years of age (63 cases) with a median age of 6 years (IQR 3-10), and 61.5% were from Lima. The previous contact was determined in 30.8% of cases. A positive SARS CoV-2 PCR result was obtained in 50.6%. The presence of comorbidity was 53.8%. The most frequent symptoms were: fever (39.6%), general malaise (23.1%), cough (19.8%), and respiratory distress (14.3%). The presence of multisystem inflammatory syndrome in children (MIS-C) was confirmed in 6 patients. Antibiotics were administered in 76.9%. The most frequent radiological pattern was bilateral interstitial infiltrates (57.7%). Mortality was higher in patients in the ICU than in the hospitalization ward (27.3% vs. 4.3%, respectively; p = 0.020)   Conclusions: COVID-19 in children presents mild and moderate clinical manifestations. The presence of comorbidity is an important factor for hospitalization, and mortality is high upon admission to critical care units.